2014
DOI: 10.1016/j.dcn.2013.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Acute exercise facilitates brain function and cognition in children who need it most: An ERP study of individual differences in inhibitory control capacity

Abstract: The present study examined the effects of moderate-intensity aerobic exercise on aspects of cognitive control in two groups of children categorized by higher- and lower-task performance. Event-related brain potentials (ERPs) were collected in 40 preadolescent children during a modified flanker task following 20 min of treadmill walking and seated rest on separate occasions. Participants were bifurcated into two groups based on task performance following the resting session. Findings revealed that following exe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
188
6
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 229 publications
(217 citation statements)
references
References 51 publications
19
188
6
4
Order By: Relevance
“…These data indicate that the manipulation of our Go/Nogo task design was appropriate and that exercise has a greater effect on the inhibitory control-related executive function than that related to basic informational processes. These findings are consistent with those from previous studies examining healthy populations and using other types of inhibitory tasks (e.g., the flanker task and the stop signal task) [28][29][30],…”
Section: Accepted Manuscriptsupporting
confidence: 93%
“…These data indicate that the manipulation of our Go/Nogo task design was appropriate and that exercise has a greater effect on the inhibitory control-related executive function than that related to basic informational processes. These findings are consistent with those from previous studies examining healthy populations and using other types of inhibitory tasks (e.g., the flanker task and the stop signal task) [28][29][30],…”
Section: Accepted Manuscriptsupporting
confidence: 93%
“…Short bouts of exercise affect cognitive processes by increasing response speed and accuracy (Tomporowski, 2003), improving working memory capacity (Pontifex, Hillman, Fernhall, Thompson, & Valentini, 2009), as well as improved performance on free-recall tasks (Coles & Tomporowski, 2008). For example, Drollette et al (2014) showed that, after 20 minutes of treadmill walking, preadolescent children had better performance on cognitive tasks gauging attention and inhibitory control compared with children who remained seated.…”
Section: Effects Of Whole-body Movementsmentioning
confidence: 99%
“…They concluded that acute bouts of physical activity might facilitate memory storage efficiency by minimizing rehearsal and shortening consolidation time. Focusing on the synergistic effects of physical activity and academic performance (Lees & Hopkins, 2013), physical activity programs incorporating short bouts of acute exercise could be effectively applied during daily school schedules to promote physical activity and enhance cognitive performance in children (Drollette et al, 2014). The role of school-based physical activity programs in increasing physical activity during the school day either through recess or breaks or by integrating physical activity with academic content has been investigated in several studies (Bartholomew & Jowers, 2011;Castelli, Hillman, Hirsch, Hirsch, & Drollette, 2011;Davis et al, 2011;Donnelly & Lambourne, 2011;Hillman et al, 2009, Kibbe et al, 2011Lambourne et al, 2013;Mahar et al, 2006;Telford et al, 2012;Vazou & Smiley-Oyen, 2014).…”
mentioning
confidence: 99%
“…intensity and duration) and qualitative (e.g. cognitive and motor demands) characteristics, most of the studies have focused on the quantitative characteristics of the physical activity (Drollette et al, 2014;Fisher et al, 2011;Hillman et al, 2009) which have been shown to positively affect the central nervous system through physiological responses to the physical activity (Hillman et al, 2008). Besides studies of quantitative characteristics, recent studies have also highlighted the positive effect of the qualitative characteristics of the physical activity, suggesting that the type of activity is also important (Budde et al, 2008;Gallotta et al, 2015;Jäger et al, 2014;Pesce et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…This knowledge has led to multiple studies seeking to improve cognitive function through different types of physical activity interventions. These studies have documented positive effects on cognitive performance in children after acute (Budde, Voelcker-Rehage, Pietraßyk-Kendziorra, Ribeiro, & Tidow, 2008;Drollette et al, 2014;Hillman et al, 2009) and chronic (Fisher et al, 2011;Hillman et al, 2014;MullenderWijnsma et al, 2016) physical activity. Even though physical activity consists of both quantitative (e.g.…”
Section: Introductionmentioning
confidence: 99%